Constructing an ontology model from relational database / Alymunirah Manap - Manap, Alymunirah (2014)
In knowledge management, ontology is one technique available for data sharing. The ontology is defined as explicit specification of a shared conceptualization. In present, ontology has started to be implemented such as semantic web, data mining and also artificial intelligent. These applications are available features for web 3.0. Currently, huge amount of database are stored in relational database for web 2.0 and for web 3.0relational database are associated with ontology model. The ontology is an important interface for advance searching management together with relational database where multiple database from different sources can be united which cannot be happened in web2.0. In order to create ontology model from scratch, there are many tools available such as protege and Neon Toolkit. However, for creating the ontology model from relational database, it involves method to apply such as in ontology engineering where the modelling is started with conceptual model, taxonomy model and visualizing with UML diagram that shows cardinality and domain-range axiom before constructed the ontology using protégé software. Knowledge modeling helps other user on how to model the ontology and this research will help them to understand the concept and rules for ontology model because it involves the conversion technique of relational database to ontology model.